MENINGKATKAN PROSES DAN HASIL BELAJAR IPA KELAS IV SD MELALUI MODEL QUANTUM TEACHING - Sundahry Puput Wahyu Hidayat Liza Septiani (Jurnal Tunas Pendidikan, 2022)
ABSTRACT The purpose of this study is to describe improving the learning process and outcomes of fourth grade students through the Quantum Teaching model at SDN 90/II Talang Pantai. This type of research is classroom action research, with the subject of class IV students at SDN 90/II Talang Pantai, totaling 23 students. This research was conducted in the even semester of the 2021/2022 Academic Year. The research instrument used was the teacher's activity observation sheet, the student's activity observation sheet. The implementation of science learning through the class IV Quantum Teaching learning model went well. Based on the results of the study, the learning process of students in the first cycle with an average of 51.41% and the second cycle 70.84%. While the learning outcomes of students increased from 47.82% in the first cycle and the second cycle to 82.60%. It can be concluded that the use of this Quantum Teaching model can improve science learning processes and outcomes. Keywords: Process, Learning Outcomes, Quantum Teaching